In Vitro Evaluation of the Antibacterial Properties of Lime Mistletoe (Dendrophthoe petandra (L.) Miq.) Extract Against Escherichia coli - Lisa Savitri; Juan Vega Mahardika; Novirma Yanti; Syntia Tanu Juwita (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
The increasing prevalence of antibiotic-resistant bacteria necessitates the exploration of alternative antimicrobial agents derived from natural sources. This study aimed to evaluate the in vitro antibacterial activity of lime mistletoe (Dendrophthoe petandra (L.) Miq.) extract against Escherichia coli ATCC 25922 using the disc diffusion method. Extract concentrations of 20%, 40%, 60%, 80%, and 100% were prepared alongside negative (distilled water) and positive (Cefadroxil) controls. Nutrient Agar (NA) media were inoculated with E. coli and discs impregnated with each concentration were placed on the media, followed by incubation at 37°C for 24 hours. The inhibition zones were measured to assess antibacterial activity. Results demonstrated a concentration-dependent increase in antibacterial efficacy, with inhibition zone diameters ranging from 8.3 mm at 20% extract to 20.3 mm at 100% extract concentration. The highest concentration’s inhibition zone was comparable to that of Cefadroxil (22.5 mm). No inhibition was observed in the negative control. Statistical analysis confirmed significant differences between treatment groups (p < 0.05). The antibacterial activity of lime mistletoe extract is likely due to its bioactive phytochemicals such as flavonoids and phenolics, which are known to disrupt bacterial cell membranes and inhibit microbial growth. These findings suggest that Dendrophthoe petandra extract holds potential as a natural antibacterial agent, providing an alternative to conventional antibiotics amid growing resistance issues. Further studies involving isolation of active compounds, toxicity evaluation, and in vivo testing are recommended to validate its clinical applicability.